SKAP2-BRAF fusion and response to an MEK inhibitor in a patient with metastatic melanoma resistant to immunotherapy. Issue 6 (24th June 2021) - Chew, Sonya Minmin; Lucas, Mairi; Brady, Michelle; Kelly, Catherine Margaret
Abstract : A woman in her 40s presented to the emergency department with headache and unintentional weight loss in September 2018. Investigations revealed a widely metastatic pan-negative melanoma of unknown primary. She had multiple lines of treatment including combination immunotherapy and chemotherapy. Next-generation sequencing identified an SKAP2-BRAF fusion protein, and she was commenced on an MEK inhibitor in September 2019 with a partial response seen on restaging scans after 6 weeks and a dramatic fall in her lactate dehydrogenase from 2248 IU/L to 576 IU/L. Unfortunately, the response was not maintained and she died from progression of her cancer in January 2020. SKAP2-BRAF fusions have a dimerisation domain that paradoxically activates the mitogen-activated protein kinase pathway, resulting in hyperproliferation if first-generation or second-generation BRAF inhibitors are used. Our knowledge is limited regarding the complex effects of targeted therapy in rare BRAF fusion proteins.